1996
DOI: 10.1007/bf01985716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of current-season application of calcitic lime on soil pH, yield and cadmium concentration in potato (Solanum tuberosum L.) tubers

Abstract: Cadmium (Cd) has accumulated in many agricultural soils in Australia due to fertilization with phosphatic fertilizers that contained Cd as an impurity. Nine field and seven glasshouse experiments using light-textured soils were conducted to investigate the effect of current-season applications of calcitic lime on i) soil pHw, ii) tuber yield, and iii) Cd accumulation in tubers of a range of processing (Russet Burbank, Atlantic, Shepody and Kennebec) and fresh market (Crystal, Pontiac and Desiree) potato cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The difference between field trials and pot experiments was stressed by Maier et al (1997). They found decreasing Cd uptake in potato tubers at increasing pH, caused by liming, under glasshouse conditions, but no effect or even increasing Cd uptake with increasing pH in field experiments.…”
Section: Uptake Of Heavy Metalsmentioning
confidence: 90%
See 1 more Smart Citation
“…The difference between field trials and pot experiments was stressed by Maier et al (1997). They found decreasing Cd uptake in potato tubers at increasing pH, caused by liming, under glasshouse conditions, but no effect or even increasing Cd uptake with increasing pH in field experiments.…”
Section: Uptake Of Heavy Metalsmentioning
confidence: 90%
“…In field trials (Andersson & Siman, 1991;McLaughlin et al, 1994;Maier et al, 1997), the effects of pH on Cd uptake often seem to be contradictory. The difference between field trials and pot experiments was stressed by Maier et al (1997).…”
Section: Uptake Of Heavy Metalsmentioning
confidence: 93%
“…Concentration of Cd in oat, ryegrass, carrot and spinach decreased with increasing soil pH in a sandy soil, but Cd concentration of ryegrass increased with increasing pH in a loam soil (He and Singh 1994a,b). In several studies, Cd uptake increased with increasing pH (Andersson and Siman 1991;Sparrow et al 1993a;Maier et al 1997). The Ca 2+ in the soil solution may have competed with Cd for sorption sites, off-setting the effect of increasing pH.…”
Section: Lime Applicationmentioning
confidence: 97%
“…Similarly, Li et al (1996) found that adding limestone to acidic soils had no effect on non-oilseed sunflower {Helianthus annum L.) grain Cd concentration. Liming did not reduce the Cd status in crops studied by Jaakola (1977) and Sparrow et al (1993), and in some instances liming has resulted in increased crop Cd concentrations (Sparrow et al 1993;Maier et al 1997). As a consequence it may be important to evaluate the effect of soil pH on plant Cd concentrations in a field situation to ascertain its true potential as a management strategy.…”
Section: Plant CD Concentrationsmentioning
confidence: 99%
“…A number of studies have shown that with increasing soil pH, there is a corresponding decrease in plant Cd concentrations (e.g., Han & Lee 1996). In contrast, however there have been several field trials in which liming to increase soil pH has resulted in no change in plant Cd concentrations (e.g., Sparrow et al 1993) and in some instances liming soil has increased plant Cd concentrations (e.g., Maier et al 1997;Singh & Myhr 1998).…”
Section: Introductionmentioning
confidence: 99%